Higher Education Effects Over Democracy Indicators - Delgado, Augusto (Theoretical and Practical Research in Economic Fields, 2026)
The purpose of this study is to examine the impact of higher education on democratic dynamics, specifically focusing on the number of national elections and the variety of political parties across 159 countries from 1990 to 2020. It aims to differentiate the effects of educational quantity from educational quality. The research utilizes a cross-sectional dataset. To address endogeneity issues, such as reverse causality and omitted variable bias, the study employs spatial autoregressive (SAR) and spatial error models (SEM). These models account for spatial dependencies and regional political norms that influence democratic outcomes. The results reveal distinct effects for education quantity and quality. A higher number of universities is associated with an increase in political parties, fostering pluralism, but does not significantly affect election frequency. Conversely, higher education quality positively correlates with election frequency and negatively with the number of parties, suggesting a “screening effect” that promotes institutional stability and consolidated party systems. This paper contributes to the literature by disaggregating higher education into quantity and quality metrics. It provides a novel application of spatial econometrics to clarify the nuanced contributions of educational infrastructure to specific democratic indicators, offering a more sophisticated understanding than traditional aggregate measures. For policymakers, the findings suggest that quantitative expansion of universities promotes political representation, while qualitative improvements are essential for institutionalizing electoral processes and reducing party fragmentation.